Cadeia de criação de valor nas empresas torrefadoras de café - Oliveira, Letícia de (2004)
The aim of this work was to propose a composition of the value creation chain for the coffee torrefaction facilities. The research was classified as exploratory, studied in a qualitative way, because the existence of studies that approach the value creation were not verified, and descriptive, because it looks forward to identifying the differentiating capacities and the financial strategies of the coffee torrefaction facilities concerning the value creation. The research in focus used a no-probabilistic sample judgement. The results were based on the answers to questionnaires sent via internet to five medium to large size torrefaction facilities and one of small size, according to SEBRAE classification. The data collection period was from august to november 2003. Concerning the general analysis of the research, it is worth to stake that this was structured with the purpose of identifying, in coffee torrefaction facilities, the differentiating capacities and the financial strategies, as well as its strategic limitations for the aggregation of value to its products. Thus, the model of creation of value was used as a parameter in the analysis of the questionnaires results. It is important to emphasize that the main differentiating capacities pointed by the researched companies refer to the purchase of the coffee, mainly from exporters and sales in supermarkets. Those companies are looking for market opportunities, they consider the quality of the products and they adopt the marketing as a criterion to increase the value of the product. Furthermore, they possess a price policy in relation to covering the total costs, because they increased the varieties of products offered to increase the market slice. The strategies developed by the torrefaction facilities are aimed to the reduction of costs and profitability. For the main financial strategies observed in the research it can be pointed out that the companies look for the decrease of costs, by means of the company growth in new financings, ha ving bank loans as source, because they need working assets. The researched companies use the profitability index for the analysis of a project and they adopt the liquidity as an economic-financial indicator. Besides, the torrefaction facilities are investing in marketing. The studied chain allows the efficient search of new market opportunities for the coffee torrefaction facilities observed financial strategies for the production and commercialization of new products.